2003
DOI: 10.1242/dev.00598
|View full text |Cite
|
Sign up to set email alerts
|

Targeted expression ofshibirets andsemaphorin 1areveals critical periods for synapse formation in the giant fiber ofDrosophila

Abstract: In order to determine the timing of events during the assembly of a neural circuit in Drosophila we targeted expression of the temperature-sensitive shibire gene to the giant fiber system and then disrupted endocytosis at various times during development. The giant fiber retracted its axon or incipient synapses when endocytosis was blocked at critical times, and we perceived four phases to giant fiber development: an early pathfinding phase, an intermediate phase of synaptogenesis, a late stabilization process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 34 publications
2
20
0
5
Order By: Relevance
“…Initially being identified as repulsive guidance molecules, several studies in the last decades have reported a chemoattractive role of semaphorins [138140]. Semaphorins guide the development of peripheral nerve projection and involved in synaptogenesis in the CNS [141, 142]. The persistence of their expression in adulthood suggests a role in the maintenance of pre-established connections and cerebral homeostasis [143].…”
Section: Interactions Of Css With Different Families Of Molecules In mentioning
confidence: 99%
“…Initially being identified as repulsive guidance molecules, several studies in the last decades have reported a chemoattractive role of semaphorins [138140]. Semaphorins guide the development of peripheral nerve projection and involved in synaptogenesis in the CNS [141, 142]. The persistence of their expression in adulthood suggests a role in the maintenance of pre-established connections and cerebral homeostasis [143].…”
Section: Interactions Of Css With Different Families Of Molecules In mentioning
confidence: 99%
“…To manipulate the level of synaptic activity, we either increased the BO excitability by expressing the heat-activated Drosophila transient-receptor-potential A1 (dTrpA) channel (23) or reduced transmitter release from BN through a temperature-sensitive form of the dominant-negative dynamin, Shibire ts ( Shi ts ) (24). These manipulations eliminated light-induced modification of LN(v) dendrites at 29°C (Fig.…”
mentioning
confidence: 99%
“…Previous anatomical studies have delineated the various developmental stages of the GFS (Allen et al, 1998; Phelan et al, 1996) (Fig. 4A) and have also identified critical periods for synapse formation (Murphey et al, 2003). We utilized the TARGET system (McGuire et al, 2004a; McGuire et al, 2004b) to regulate UAS- ben expression during different stages of GF development.…”
Section: Resultsmentioning
confidence: 99%